Epilepsy in multiple sclerosis: The role of temporal lobe damage. (March 2017) - Calabrese, M; Castellaro, M; Bertoldo, A; De Luca, A; Pizzini, FB; Ricciardi, GK; Pitteri, M; Zimatore, S; Magliozzi, R; Benedetti, MD; Manganotti, P; Montemezzi, S; et al.
Background: Although temporal lobe pathology may explain some of the symptoms of multiple sclerosis (MS), its role in the pathogenesis of seizures has not been clarified yet. Objectives: To investigate the role of temporal lobe damage in MS patients suffering from epilepsy, by the application of advanced multimodal 3T magnetic resonance imaging (MRI) analysis. Methods: A total of 23 relapsing remitting MS patients who had epileptic seizures (RRMS/E) and 23 disease duration matched RRMS patients without any history of seizures were enrolled. Each patient underwent advanced 3T MRI protocol specifically conceived to evaluate grey matter (GM) damage. This includes grey matter lesions (GMLs) identification, evaluation of regional cortical thickness and indices derived from the Neurite Orientation Dispersion and Density Imaging model. Results: Regional analysis revealed that in RRMS/E, the regions most affected by GMLs were the hippocampus (14.2%), the lateral temporal lobe (13.5%), the cingulate (10.0%) and the insula (8.4%). Cortical thinning and alteration of diffusion metrics were observed in several regions of temporal lobe, in insular cortex and in cingulate gyrus of RRMS/E compared to RRMS ( p < 0.05 for all comparisons). Conclusions: Compared to RRMS, RRMS/E showed more severe damage of temporal lobe, which exceeds what would be expected on the basis of the global GM damage observed.